Factors associated with the metabolically obese thin phenotype in Peruvian inhabitants - Guerra Valencia, Jamee; Torres Malca, Jenny Raquel; Talavera, Jesus E.; Zuzunaga-Montoya, Fiorella E.; De La Cruz Vargas , Jhony Alberto; Vera-Ponce, Víctor Juan (Medicina Clínica y Social, 2022)
Introduction: Patients with the lean metabolically obese (BMD) phenotype may present the same risk as the classic obese for developing long-term chronic diseases. However, the prevalence and the factors that are associated with it vary according to the population studied. Objective: to determine the prevalence and the factors associated with the BMD phenotype in Peru. Methods: Cross-sectional analytical study. Secondary analysis of the PERU MIGRANT study database. The associated factors that were considered were: age (30-44 years, 45-59 years, and 60 years and over), sex, socioeconomic status, level of education, migration, smoking, alcohol consumption and level of physical activity. Results: The prevalence of the BMD phenotype was 32.23% (95% CI 27.61-37.10). In the multivariate analysis, the male sex showed a 39% lower probability of presenting the BMD phenotype (PRa: 0.610; 95% CI 0.428-0.869; p=0.006), compared to the female sex. While belonging to the age groups between 45-59 years and 60 years and over presented 110.5% (PRa: 2.105; 95% CI 1.484-2.988; p<0.001) and 97.6% (PRa: 1.976; CI95% 1.270-3.075; p=0.003), respectively, greater probability of presenting BMD, compared to the group of 29-44 years. Conclusions: Belonging to the female sex and to the age groups of 45 to 59 and 60 years or more, increased the probability of presenting the BMD phenotype. Future prospective studies with a larger sample size are recommended to confirm these findings, as well as the inclusion of new variables.